The Effectiveness of Educational Development in the New Normal in Selected Schools in Marawi City, Philippines - Modiaba, Mohammad Asnoden; Barangai, Omerah (Journal of Interdisciplinary Perspectives, 2025)
The COVID-19 pandemic profoundly reshaped education, compelling schools in Marawi City, Lanao del Sur, to transition to remote learning under the "new normal." While the challenges of remote learning are globally recognized, a localized, in-depth analysis of its specific impact on student academic performance and instructional barriers within Marawi City remained a key knowledge gap. This study assessed the pandemic’s effects on educational development, focusing on educators’ profiles, students’ academic performance, challenges, and instructional adaptations. Using a quantitative-descriptive design with survey data from public and private teachers, the results showed that most respondents were female, aged 26–35, with 1–5 years of service. Moderate improvement in students’ performance was noted, attributed to multimedia and interactive approaches. However, limited internet access, lack of in-person interaction, and reduced motivation were significant barriers. The study emphasizes the need for flexible, innovative strategies in technological support, teacher training, and stakeholder engagement to sustain quality education amid crises.